2013
DOI: 10.1111/jmi.12033
|View full text |Cite
|
Sign up to set email alerts
|

Temperature measurement in the microscopic regime: a comparison between fluorescence lifetime‐ and intensity‐based methods

Abstract: SummaryThermally sensitive fluorescent indicators have been proposed to monitor temperature changes in microfluidic systems, mainly based on fluorescence intensity or lifetime. However, measuring temperature in a structured environment, such as biological tissue, presents additional challenges due to the chemical and structural complexity. Here, we investigate the potential for resolving temperature distributions within the volume of a single cell. Rhodamine B (RhB) dye was employed as a temperature indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 47 publications
1
31
0
1
Order By: Relevance
“…The same conclusion was also inferred by Rai and Rai in Pr 3+ ‐doped lithium tellurite glass, Paviolo et al in fluorescent molecular thermometers based on rhodamine B (RhB) and by Gálico et al in the [Eu(bzac) 3 (H 2 O) 2 ] complex (where bzac − stands for tris(1‐phenyl‐1,3‐butanedione). Paviolo et al realized that the temperature in an organic tissue's cytoplasm measured via RhB emission intensity is more precise and reliable than that measured using the RhB lifetime, while Gálico et al reported S m = 5.25% K −1 (at 303 K) and S m = 1.35% K −1 (at 293 K) through the temperature dependence of the integrated intensity of the 5 D 0 → 7 F 2 transition and the 5 D 0 lifetime, respectively. Recently, Gharouel et al performed a systematic comparison of the performance of distinct Pr 3+ ‐based thermometers operating over 298–363 K using either the thermal dependence of the ratio of two 4f transitions or of the decay time of an excited state.…”
Section: Sensing Temperature With Luminescencesupporting
confidence: 73%
See 1 more Smart Citation
“…The same conclusion was also inferred by Rai and Rai in Pr 3+ ‐doped lithium tellurite glass, Paviolo et al in fluorescent molecular thermometers based on rhodamine B (RhB) and by Gálico et al in the [Eu(bzac) 3 (H 2 O) 2 ] complex (where bzac − stands for tris(1‐phenyl‐1,3‐butanedione). Paviolo et al realized that the temperature in an organic tissue's cytoplasm measured via RhB emission intensity is more precise and reliable than that measured using the RhB lifetime, while Gálico et al reported S m = 5.25% K −1 (at 303 K) and S m = 1.35% K −1 (at 293 K) through the temperature dependence of the integrated intensity of the 5 D 0 → 7 F 2 transition and the 5 D 0 lifetime, respectively. Recently, Gharouel et al performed a systematic comparison of the performance of distinct Pr 3+ ‐based thermometers operating over 298–363 K using either the thermal dependence of the ratio of two 4f transitions or of the decay time of an excited state.…”
Section: Sensing Temperature With Luminescencesupporting
confidence: 73%
“…The most used method to calculate the absolute temperature through thermographic phosphor thermometry is by measuring the luminescence intensities of two electronic transitions (occasionally involving Stark components of an excited electronic state) in thermal equilibrium (see Section ). Moreover, different phosphors have been examined for providing a contactless thermal reading through their light emission properties, e.g., polymers, DNA or protein conjugated systems, organic dyes, quantum dots (QDs), Cr 3+ ‐based materials, and trivalent lanthanide (Ln 3+ ) ions (for a recent review see ref. ).…”
Section: Introductionmentioning
confidence: 99%
“…Luminescence thermometry is being addressed as one of the most promising techniques to measure the temperature with submicrometric resolution, because it can combine both high spatial and temporal resolution with a robust measurement based on the temperature dependence of the steady-state emission [9,12,18], lifetime [17,[19][20][21] and risetime [22]. It is unquestionable that the wisest luminescent nanothermometry choice should produce a ratiometric intensity response to temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that progress in the development of intracellular temperature measurement techniques, including FPTs, will provide a better understanding of hyperthermia, thus making it a more versatile and effective treatment method. intracellular temperature, fluorescence, imaging, polymer 温度は,様々な生理機能に影響を与える最も重要な因子の一つである.熱を加えて癌治療を行う温熱 療法"ハイパーサーミア"は,生物学における温度の重要性を細胞-組織-生体という全てのスケール Table I に示す.これらはいずれも細胞内での温 度応答性が確認されている細胞内温度測定用の蛍光性温度計である.感温性高分子 2,4-9) ,Eu 錯体 10-13) , 量子ドット [14][15][16]) ,蛍光タンパク質 [17][18][19][20] ,DNA 21) ,ナノダイヤモンド 22) ,低分子化合物 [23][24][25][26] 2) Gota C., Okabe K., Funatsu T., Harada Y., Uchiyama S.: Hydrophilic fluorescent nanogel thermometer for intracellular thermometry. J Am Chem Soc, 131: 2766-2767, 2009.…”
unclassified